Women, family and family businesses across entrepreneurial contexts - Le Loarne-Lemaire, Séverine; Brush, Candida G.; Calabrò, Andrea; Maalaoui, Adnane (Edward Elgar Publishing, 2022)
"The expert contributors to this insightful book explore the latest research on women's emancipation through entrepreneurship, specifically in relation to families and family businesses. The chapters analyse the role the family plays and how women interact with their families in developing their entrepreneurial projects or taking over the lead of the family business. They examine key themes such as the role of religion, women's agency, business succession, and identity. To illustrate these areas, the book draws on case studies from a wide variety of contexts, including Syrian women refugee entrepreneurs, Tunisian women entrepreneurs and entrepreneurial parents working from home. The book also draws attention to previously underexplored topics in women's entrepreneurship, such as spousal support. Looking to future research, it calls for a better understanding of what emancipation means for women in different contexts. This book will be a useful resource for scholars and students of entrepreneurship with a particular interest in family business. Its use of global case studies will also be beneficial for practitioners in this field as well as networks of women entrepreneurs"--